A portable high-intensity focused ultrasound system for the pancreas with 3D electronic steering: a preclinical study in a swine model - Chang, Won; Lee, Jae Young; Lee, Jae Hwan; Bae, Jae Seok; Cho, Yeon Jin; Kang, Kook Jin; Son, Keonho; Chung, Yul Ri; Lee, Kyoung Bun; Han, Joon Koo (Ultrasonography (Seoul, Korea), 2018)
The aim of this animal study was to evaluate the safety and feasibility of a portable, ultrasonography-guided, high-intensity focused ultrasound (USg-HIFU) system to treat the pancreas. Eight swine were included. Using a portable HIFU device (ALPIUS 900, Alpinion Medical Systems), ablations were performed on the pancreas in vivo. Different acoustic intensities were applied (1.7 kW/cm2 or 1.5 kW/cm2 , n=2 [group A for a pilot study]; 1.5 kW/ cm2 , n=3 [group B]; and 1.2 kW/cm2 , n=3 [group C]). Magnetic resonance imaging (MRI) was performed immediately (group A) or 7 days (groups B and C) after HIFU treatment. In groups B and C, serum amylase and lipase levels were measured on days 0 and 7, and performance status was observed every day. Necropsy was performed on days 0 (group A) or 7 (groups B and C) to assess the presence of unintended injuries and to obtain pancreatic and peripancreatic tissue for histological analysis. Ablation was noted in the pancreas in all swine on MRI, and all pathologic specimens showed coagulation necrosis in the treated area. The mean ablation areas on MRI were 85.3±38.1 mm2, 90.7±21.2 mm2, and 54.4±30.6 mm2 in groups A, B, and C, respectively (P>0.05). No animals showed evidence of complications, except for one case of a pseudocyst in group B. This study showed that pancreas ablation using a portable USg-HIFU system may be safe and feasible, and that coagulation necrosis of the pancreas was successfully achieved with a range of acoustic intensities.